Effect of long-term chronic hyperhomocysteinemia on retinal structure and function in the cystathionine-β-synthase mutant mouse. (January 2022) - Xiao, Haiyan; Wang, Jing; Barwick, Shannon R.; Yoon, Yisang; Smith, Sylvia B.
Abstract: Elevated levels of the excitatory amino acid homocysteine (Hcy) have been implicated in retinal diseases in humans including glaucoma and macular degeneration. It is not clear whether elevated Hcy levels are pathogenic. Models of hyperhomocysteinemia (Hhcy) have proven useful in addressing this including mice with deficiency in the enzyme cystathionine β-synthase (CBS). Cbs +/- mice have a ∼two-fold increase in plasma and retinal Hcy levels. Previous studies of visual function and structure in Cbs +/- mice during the first 10 months of life revealed mild ganglion cell loss, but minimal electrophysiological alterations. It is not clear whether extended, chronic exposure to moderate Hhcy elevation will lead to visual function loss and retinal pathology. The present study addressed this by performing comprehensive analyses of retinal function/structure in 20 month Cbs +/- and Cbs +/+ (WT) mice including IOP, SD-OCT, scotopic and photopic ERG, pattern ERG (pERG), and visual acuity. Eyes were harvested for histology and immunohistochemical analysis of Brn3a (ganglion cells), dihydroethidium (oxidative stress) and GFAP (gliosis). The analyses revealed no difference in IOP between groups for age/strain. Visual acuity measured ∼0.36c/d for mice at 20 months in Cbs +/- and WT mice; contrast sensitivity did not differ between groups at either age. Similarly SD-OCT, scotopic/photopic ERG and pERG revealed no differences between 20 month Cbs +/- and WT mice. There was minimal disruption in retinal structure when eyes were examined histologically. Morphometric analysis revealed no significant differences in retinal layers. Immunohistochemistry revealed ∼5 RGCs/100 μm retinal length in both Cbs +/- and WT mice at 20 months. While there was greater oxidative stress and gliosis in older (20 month) mice versus young (4 month) mice, there was no difference in these parameters between the 20 month Cbs +/- and WT mice. We conclude that chronic, moderate Hhcy (at least due to deficiency of Cbs ) is not accompanied by retinal structural/functional changes that differ significantly from age-matched WT littermates. Despite considerable evidence that severe Hhcy is toxic to retina, moderate Hhcy appears tolerated by retina suggesting compensatory cellular survival mechanisms. Highlights: Excess levels of homocysteine (Hcy), an excitatory amino acid, have been implicated retinal diseases such as glaucoma and macular degeneration, but it is not clear if Hcy is a biomarker or pathogenic in these diseases. The current study examined effects on retinal structure and function in aged (20 months) Cbs ± mice with deficiency of cystathionine β-synthase, which leads to moderate elevation of Hcy. Comprehensive assessment of intraocular pressure, visual acuity, in vivo retinal structure (SD-OCT), and electrophysiology (ERG, pERG) showed no difference between 20 month Cbs ± and age-matched WT mice. Systematic morphometric analysis and immunodetection for cellular stress showed similar results between 20 month Cbs ± and age-matched WT mice. While high levels of Hcy are toxic to retina, moderate Hcy levels due to CBS deficiency do not appear to have deleterious impact on retinal structure/function in aged mice and may be a biomarker rather than pathogenic.